RISIKO USAHATANI TOMAT PADA MUSIM PENGHUJAN DI DESA ALIMMEBUNG KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Emi Rensiana Latuan; Andri P. Timung; Moses Duli Weni (Partner, 2022)
The risk of agricultural production is greater than the risk of non-agriculture, because agriculture is strongly influenced by nature such as weather, pests and diseases. The research sample used the Slovin formula so that the number of samples was 44 tomato farmers. This study aims to determine the risk of tomato farming in the rainy season in Alimmebung Village, Alor Tengah Utara District, Alor Regency. The data obtained were analyzed using the formula of variance or standard deviation and the Coefficient of Variation. Tomato cultivation in Alimmebung Village is planted in two seasons, namely the dry season and the rainy season. In the rainy season there are many risks, one of which is the risk of income due to high soil moisture, causing pests and diseases to plants. Judging from the existing CV which is 0.03 then (0.5) so that tomato farmers in Alimmebung Village do not experience losses when planting tomatoes in the rainy season.Key Words : Tomato.Coefficient of Variation, Alimmebung